The Semantics of word formation and lexicalization - Hacken, Pius ten; Thomas, Claire (Edinburgh University Press, 2013)
In this book, the focus is on the semantic aspect of the formation of new words rather than on generating the form as is more traditional. Each chapter concentrates on a specific question about a theoretical concept or a word formation process in a particular language and adopts a theoretical framework that is appropriate to the study of this question.